2020
DOI: 10.1016/j.electacta.2020.136852
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrochemical studies of functionalization of reduced graphene oxide with alkoxyphenylporphyrin mono- and tetra- carboxylic acid: application to DNA sensors

Abstract: Association of graphene with conjugated organic macromolecules presents an interest in various applications. Here, we study the chemical and electrical properties of nanomaterials which combine the features of chemical reduced graphene oxide (CRGO) and its modification with tetrabutyloxyphenylporphyrins bearing a mono-or tetra-carboxylic functions. The hybrid nanomaterials are characterized through different techniques including UV-visible, FT-IR, Raman spectroscopy, MEB and SEM. Their electrochemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Measurements using several independent biosensors were used to assess the reproducibility of this DNA hybridization platform. 221 Various studies using rGO-porphyrin and GQD-Pp composite have been reported for the electrochemical sensing of serotonin, dopamine, and glucose sensing, demonstrating enhanced selectivity and sensitivity towards these analytes. 222,223 Zhang et al developed a "turn-ON" fluorescence sensor via optical sensing for the detection of hydrogen peroxide (H 2 O 2 ) and glucose using a GQD/FeTMPyP hybrid system (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…Measurements using several independent biosensors were used to assess the reproducibility of this DNA hybridization platform. 221 Various studies using rGO-porphyrin and GQD-Pp composite have been reported for the electrochemical sensing of serotonin, dopamine, and glucose sensing, demonstrating enhanced selectivity and sensitivity towards these analytes. 222,223 Zhang et al developed a "turn-ON" fluorescence sensor via optical sensing for the detection of hydrogen peroxide (H 2 O 2 ) and glucose using a GQD/FeTMPyP hybrid system (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…A nanocomposite material consisting of CrGO and tetraphenylporphyrin derivatives, bearing one or four butyloxyphenyl groups, was prepared and fully characterized by Korri-Youssoufi's group [34]. The presence of these peripheral groups on the porphyrin skeleton improved both the dispersibility and the electron transfer ability.…”
Section: Other Application For Graphene-porphyrin Hybridsmentioning
confidence: 99%
“…where c, L and C are speed of the light in vacuum, capacitance and inductance, respectively. Enhancing Ef1 would diminish the inductance value L [25], which would decrease the absorption peak wavelength according to (6). Considering Ef1=0.9ev, the short wavelength ranges of 30-45µm with 97% absorption peak and long wavelength ranges of 45-60µm with 94% peak, would be achieved.…”
Section: A First Structurementioning
confidence: 99%
“…Indeed, SPR-refractive index (SPR-RI) biosensors have attracted extreme attentions [2]. Biosensors can be utilized as diagnosis instruments, clinical and lab detection devices [3,4], and also for sensing various bio-molecules such as proteins [5], DNA [6] and other vital tissues. SPR based sensors have interesting and appropriated specifications that make them good candidates for bio-sensing applications.…”
Section: Introductionmentioning
confidence: 99%